Peculiarities of the National Agency for the Prevention of Corruption Activities under Martial Law (Law and Safety, 2023)
In the article, the authors identified and analyzed the main features of the activities of the National Agency for the Prevention of Corruption under martial law.The authors proved that after the full-scale invasion of Russia, the National Agency for the Prevention of Corruption, as well as most state bodies, has adapted to the changes in the state and society. The authors note that a wide range of powers and rights of the National Agency for the Prevention of Corruption are fixed at the legislative level. In the scientific article, the authors have conditionally divide the entire set of rights and powers of the National Agency for the Prevention of Corruption into types “depending on the scope of their implementation or depending on the function within they are carried out”. It has been emphasized that in the conditions of martial law, the National Agency for the Prevention of Corruption continued to fulfill its powers, using the rights enshrined in Article 12 of the Law of Ukraine “On Prevention of Corruption”. However, taking into account the military and political situation that has led to the emergence of new social relations or the change of existing ones (crossing the border by men of military age under martial law, the activities of charitable and humanitarian funds, etc.), the content of the powers of the National Agency for the Prevention of Corruption has been transformed to a certain extent. In the conditions of martial law, despite the partial temporary suspension of certain functions, the National Agency for the Prevention of Corruption not only continues to fulfill its mandate, but also redistributes resources for wartime needs. It has been proven that the essence of the activity of the National Agency for the Prevention of Corruption in the conditions of martial law has remained unchanged, ensuring the formation and implementation of the state anti-corruption policy, the formation of rules for the prevention of corruption and the improvement of the transparency of the public sector.
Keywords: rights of the National Agency for the Prevention of Corruption; powers of the National Agency for the Prevention of Corruption; National Agency for the Prevention of Corruption; martial law.